Phytochrome and Hormone Signaling Crosstalk in Response to Abiotic Stresses in Plants - Gavassi, Marina Alves [UNESP]; Alves, Frederico Rocha Rodrigues; Carvalho, Rogério Falleiros [UNESP] (Springer Nature, 2023)
Linking plant light perception to molecular and biochemical responses, multiple signaling pathways are triggered, especially considering the participation of hormones downstream of phytochromes, the most extensively characterized plant photoreceptors. It has been shown that the interaction between phytochrome and hormones modulates plant development, from seed germination to flowering, in response to a plethora of abiotic stresses, the most worrisome factors for agricultural traits. In this chapter, we provide an overview of the interaction between the main molecular components shared between phytochrome and plant hormone signaling pathways during heat, low temperature, drought, and salt stresses, discussing interesting points which raise perspectives for plant tolerance bioengineering.
Keywords: Drought stress; Heat stress; Light signaling; Low-temperature stress; Phytochrome-interacting factors; PIFs; Salt stress